Environmental Media Messages in UNESA’s Green & Clean Movement to Support SDG 12.5 - Wulandari, Insiatul Fa'anit; Fitrihidajati, Herlina; Candra, Adi; Nurcholis, Nurcholis; Aseyan, Aseyan (Universitas Muhammadiyah Malang, 2026)
Environmental message media programs aim to foster students' attitudes of environmental care. Waste management within the campus environment remains a major challenge in realizing a sustainable Green Campus concept. This study aims to analyze the role of environmental message media in supporting the Green and Clean movement as an effort to cultivate environmental awareness among Biology students at Universitas Negeri Surabaya, particularly regarding campus cleanliness and waste management. The study employed a quantitative approach using a one-group pretest–posttest design. The intervention was implemented through the installation of educational banners and waste-sorting labels in strategic areas of the Biology Building, FMIPA UNESA, containing positive persuasive messages about cleanliness and environmental conservation, along with clean-up and waste recycling activities. The results indicate a statistically significant increase in students' levels of awareness and participation in environmental management after the intervention, although the observed improvement was not statistically significant. Environmental message media with attractive and contextual designs were shown to enhance students' attention, understanding, and emotional engagement with campus cleanliness issues. This study provides an initial overview of the effectiveness of visual communication in building a culture of environmental care in higher education settings and supports the implementation of SDGs 12.5 through waste reduction, prevention, and recycling activities.